Hubungan Lama Kerja dan Pengetahuan Bidan tentang Alat Kontrasepsi Implan dengan Kemampuan Pemasangan Implan - Iman Surihartini; Sri Rahayu; Ni Komang Yuni Rahyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
The success of implant insertion is influenced by the skills of midwives as health workers. Factors such as length of service and level of knowledge are thought to be related to midwives' skills in implant insertion. The purpose of this study was to determine the relationship between length of service and midwives' knowledge of contraceptive implants with their skills in implant insertion. This study was a quantitative correlation study with a cross-sectional design. The population in this study was all midwives in the Darek Community Health Center working area, and the sample was determined using total sampling technique, where the entire population was used as the sample. The number of samples obtained was 49 midwives in the Darek Community Health Center working area. The data were analyzed using Fisher's exact test. The results of this study indicate a significant relationship between length of service and skills (p-value = 0.002) and knowledge and skills (p-value = 0.002). This study proves that there is a significant relationship between length of service and midwives' knowledge and skills in implanting contraception. The longer the work experience and the better the midwife's knowledge, the better the skills in implanting contraceptive implants tend to be.